2022
DOI: 10.7759/cureus.25935
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib in the Treatment of Erdheim Chester Disease: A Systematic Review

Abstract: Erdheim Chester disease (ECD) is a type of histiocytosis characterized by a variable clinical presentation. The treatment of ECD is complex and mainly unknown. We aim to conduct a literature review of the treatment of ECD and consolidate the knowledge about the most recent and updated treatment for ECD. To conduct the systematic review, we used the preferred reporting items for systematic reviews and metaanalysis (PRISMA) protocol.To analyze the bias, we used the Cochrane collaboration risk-of-bias tool to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“… 5 , 6 For patients with BRAF V600E alteration and cardiac or neurologic disease or end-organ dysfunction, BRAF inhibitor therapy with tyrosine kinase inhibitors, vemurafenib, or dabrafenib should be used as first-line therapy. 1 , 9 , 10 For patients with cardiac or neurologic involvement but without genetic alterations, empiric treatment with MEK inhibitors (cobimetinib, trametinib, binimetinib, and selumetinib) should be considered. 1 …”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 For patients with BRAF V600E alteration and cardiac or neurologic disease or end-organ dysfunction, BRAF inhibitor therapy with tyrosine kinase inhibitors, vemurafenib, or dabrafenib should be used as first-line therapy. 1 , 9 , 10 For patients with cardiac or neurologic involvement but without genetic alterations, empiric treatment with MEK inhibitors (cobimetinib, trametinib, binimetinib, and selumetinib) should be considered. 1 …”
Section: Discussionmentioning
confidence: 99%
“…13 The refinement of treatment approaches and the increased awareness of ECD have led to a dramatic improvement in prognosis. 13 In general, initiation of therapy is recommended for all patients rather than observation, with the uncommon exception of patients with asymptomatic disease. Despite the availability of new treatment, it is difficult to design a proper treatment algorithm, mainly due to the absence of randomized controlled trials which are difficult to perform in such a rare disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that vemurafenib is effective for ECD patients with orbital involvement, but not for ECD with multiple organs involvement 10 . Therefore, ECD should be diagnosed and treated early, combined with IFN‐α, vemurafenib, glucocorticoids and surgical treatment to prolong the survival of patients 13 . The refinement of treatment approaches and the increased awareness of ECD have led to a dramatic improvement in prognosis 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations